Plasma homocysteine, measurement and clinical application - Hill, D. M. (Cranfield University, 2006)
Raised plasma homocysteine (Hcy) levels have been cited as a major risk factor for several vascular disorders. Yet hyperhomocysteinaemia is easily treated through dietary intervention and vitamin supplementation. Commercial assays have facilitated routine plasma Hcy analysis. However, the problem faced by clinicians is stabilisation of Hcy in whole blood samples prior to delivery to the laboratory. Following blood collection, erythrocytes continue to produce and excrete Hcy increasing plasma concentrations by up to 10% per hour. This thesis describes the investigation of stabilising plasma Hcy in whole blood, allowing wide scale screening for hyperhomocysteinaemia. The most effective method appears to be inhibition of the enzyme responsible for Hcy production, Sadenosylhomocysteine hydrolase (SAHH), using a competitive inhibitor 3- deazaadenosine (3DA). Clinical trials were conducted on a pilot batch of evacuated blood tubes. Samples were stored in EDTA whole blood in the presence and absence of 3DA, at ambient temperatures (20 to 25ºC), and under refrigerated conditions (2 to 8ºC). Only samples that were collected into EDTA plus 3DA tubes and stored refrigerated showed stability over 72 hours (p = 0.2761). For wide scale screening, samples must be stable under ambient conditions. As the structure of SAHH is known a molecular modelling approach was adopted in an attempt to identify other potential inhibitors from screened databases. Interference of SAHH, in an immunochemical method for Hcy, was to be utilised for in vitro screening before any further clinical trials were conducted. The thesis also focuses on Hcy as a marker of vitamin deficiency and explores links between thiol metabolism and the development of cognitive decline eventually leading to dementia. Disruption of single carbon metabolism can lead to an increase in Hcy and a decrease in available methyl groups important in regulation of several metabolic pathways. Increased oxidative stress may also be a causative factor.